2011
DOI: 10.3109/03602532.2011.608682
|View full text |Cite
|
Sign up to set email alerts
|

The fourth mammalian molybdenum enzyme mARC: current state of research

Abstract: The mitochondrial amidoxime-reducing component (mARC) is a recently discovered molybdenum-containing enzyme in mammalians. Upon reconstitution with the electron transport proteins, cytochrome b(5) and its reductase, this molybdenum enzyme is capable of reducing N-hydroxylated compounds. It was named mARC because the N-reduction of amidoxime structures was initially studied using this isolated mitochondrial enzyme. All hitherto analyzed mammalian genomes harbor two mARC genes: molybdenum cofactor (Moco) sulfera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
57
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 157 publications
4
57
0
1
Order By: Relevance
“…Therefore, we conclude that mARC-1 reduces nitrite to NO in the molybdenum active site, and Cys-273 is an integral amino acid of this site, presumably required for direct coordination to the molybdenum. Assuming the mARC active site is the same as sulfite oxidase, as predicted (27), removing the molybdenum coordinating cysteine ligand probably produce an oxygen-coordinated ligand (from water) (28). This mutation of the active site cysteine to alanine in sulfite oxidase family enzymes abolishes catalytic activity and has been demonstrated with sulfite oxidase (28), Chlamydomonas reinhardtii ARC (29), and similar molybdopterin enzymes.…”
Section: No Formation From Nitrite Is Limited By Marc-1 Concentrationmentioning
confidence: 59%
“…Therefore, we conclude that mARC-1 reduces nitrite to NO in the molybdenum active site, and Cys-273 is an integral amino acid of this site, presumably required for direct coordination to the molybdenum. Assuming the mARC active site is the same as sulfite oxidase, as predicted (27), removing the molybdenum coordinating cysteine ligand probably produce an oxygen-coordinated ligand (from water) (28). This mutation of the active site cysteine to alanine in sulfite oxidase family enzymes abolishes catalytic activity and has been demonstrated with sulfite oxidase (28), Chlamydomonas reinhardtii ARC (29), and similar molybdopterin enzymes.…”
Section: No Formation From Nitrite Is Limited By Marc-1 Concentrationmentioning
confidence: 59%
“…Therefore, it is well accepted that it plays a major role in N-reductive metabolism (46). However, its endogenous substrates are as yet unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in tissues of different species showed that at least one isoform of mARC was detectable in mitochondria (Da Cruz et al, 2003;Havemeyer et al, 2006;Wahl et al, 2010;Havemeyer et al, 2011;Krompholz et al, 2012;Neve et al, 2012). mARC-2 is also localized in peroxisomes (Islinger et al, 2007;Wiese et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Eukaryotic molybdenum enzymes are classified by the coordination chemistry of the molybdenum atom of Moco in two groups: the xanthine oxidoreductase family and the sulfite oxidase family. mARC proteins are regarded as members of the sulfite oxidase family (ChamizoAmpudia et al, 2011;Havemeyer et al, 2011;Rajapakshe et al, 2011;Mendel and Kruse, 2012).…”
Section: Introductionmentioning
confidence: 99%